Proust's English - Karlin, Daniel, 1953- (OUP E-Books., 2005)
A fascinating study of English words and phrases in A la recherche du temps perdu, dealing both with the social comedy of French 'Anglomania' - characters who yearn to resemble 'un parfait gentleman' or invite each other to 'le five-o'clock tea' - and with Proust's profound understanding of the necessary 'impurity' of all languages and artistic creation. Karlin demonstrates that English is a significant presence in this greatest of French. masterpieces. - ;English is the 'second language' of A la recherche du temps perdu. Although much has been written about Proust's debt to English literature.